Subsynchronous resonance oscillations mitigation via fuzzy controlled novel braking resistor model - Mohamed Fayez; M. Mandour; M. El-Hadidy; F. Bendary (International Journal of Advances in Applied Sciences, 2019)
Subsynchronous resonance (SSR) torsional torque oscillations is a problem of a great concern in the power engineering community. SSR causes torsional torque oscillations with ever-increasing magnitudes occurring in the machine shaft sections causing a premature fatigue life expenditure of the shaft metal. In this paper, dynamic braking switching strategy designed through fuzzy logic control theory and implemented via novel braking resistor model, namely chopper rectifier controlled braking resistor for tempering SSR torsional torque oscillations of a large turbo-generator. The proposed mitigation scheme has been tested on the IEEE second benchmark model for SSR studies. Comparative simulation study via MATLAB/Simulink-based modeling and simulation environment of the test model with and without the suggested mitigation regime should demonstrate its effectuality for mitigation of SSR torsional torque oscillations.